Roles and Responsibilities of Notaries in Distributing Inheritance through Making Inheritance Statements for Chinese Groups in the City of Semarang - Pradana, M.Iqbal Aditya (Jurnal Konstatering, 2023)
The inheritance statement made by a notary for the Chinese group is very useful in legal activities, especially in managing the heir's inheritance. This writing aims to find out and analyze the role and responsibilities of notaries in distributing inheritance through making inheritance statements for Chinese groups in Semarang City and what are the obstacles and solutions to the role and responsibilities of Notaries in distributing inheritance through making inheritance statements for Chinese groups in Semarang City. The approach method used in this research is a sociological juridical approach, meaning research carried out on the real conditions of society or the community environment with the aim and purpose of finding facts which then lead to identification and ultimately lead to problem solving. The analytical tools in this writing use the theory of justice, the theory of responsibility and the theory of legal certainty. The results of this research show that the role of a notary in distributing inheritance through making inheritance statements for the Chinese group in the city of Semarang is as a medium for the birth of an authentic deed, including a certificate of inheritance for the Chinese group in the city of Semarang. Notaries are not required to carry out their official duties to investigate the truth of the identity, the truth of the material contents of the deed, and the authentic deed will be proof that an event or relationship has occurred between the parties and the notary's responsibility for the distribution of inheritance through making inheritance statements for Chinese groups in the city of Semarang is limited to at the beginning of the Deed/head of the Deed and the end/closing of the deed, and full responsibility for its contents and the Notary's Obstacles in Distribution of Inheritance through making Inheritance Certificates for Chinese Groups in the City of Semarang, including: 1) The Notary does not master and understand the provisions related to heir certificates, 2) The Notary has difficulty ascertaining whether the witnesses presented are appropriate. or not, 3) There is no unification regarding the implementation arrangements for making Certificates of Inheritance Rights and 4) There are witnesses or heirs who are not honest in giving information. In connection with the obstacles that occur regarding the preparation of certificates of inheritance rights for Chinese groups by Notaries, there are several ways to overcome these obstacles. Keywords: Heir; Notary; Role.